Le taux de croissance de l’offre de monnaie et arbitrage entre le taux d’inflation et le taux de chômage au Canada - Marchon, Maurice (L'Actualité économique, 1979)
This paper presents simulations results using a "Modified St. Louis Model" for Canada. These simulations identify opportunities of trade-off between inflation and unemployment rate. They reveal very slim opportunities of trade-off and demonstrate that any short-term gain in real output caused by monetary stimulus will have to be paid in term of compensating slower output growth to reduce inflationary expectations. This situation of no real trade-off shows up even if the model does not fully endogenize the exchange rate and international trade feedback of changes in money supply growth rate.